Eesti Bariaatrilise ja Metaboolse Kirurgia Seltsi 2011. aasta soovitused rasvunud haige käsitluseks - Sillakivi, Toomas; Kaur, Ilmar; Trudnikov, Andre (Eesti Arst, 2012)
Eesti Arst 2012; 91(3):162–163